2012
DOI: 10.3109/09553002.2012.715785
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of DNA strand breaks due to direct and indirect effects of Auger electrons from incorporated123I and125I radionuclides using the Geant4 computer code

Abstract: The results are in reasonable agreement with previous experimental and theoretical results which shows the applicability of the Geant-DNA toolkit in nanodosimetry calculations which benefits from the open-source accessibility with the advantage that the DNA models used in this work enable us to save the computational time. Also, the results showed that the simpler geometry is suitable for direct break calculations, while for the indirect damage yield, the more precise model is preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…http Besides, Geant4 (GEometry ANd Tracking 4) is the only opensource and general-purpose toolkit able to simulate particle interactions with matter in a broad range of energies [25][26][27]. Also, by using the Geant4-DNA extension, the Geant4 toolkit can be utilized for simulation of early biological damage induced by ionizing radiation at micrometric and nanometric scale such as DNA [28,29]. Capability of the Geant4-DNA in microdosimetry and nanodosimetry fields has been investigated in some previous studies [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…http Besides, Geant4 (GEometry ANd Tracking 4) is the only opensource and general-purpose toolkit able to simulate particle interactions with matter in a broad range of energies [25][26][27]. Also, by using the Geant4-DNA extension, the Geant4 toolkit can be utilized for simulation of early biological damage induced by ionizing radiation at micrometric and nanometric scale such as DNA [28,29]. Capability of the Geant4-DNA in microdosimetry and nanodosimetry fields has been investigated in some previous studies [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…This cylindrical approach was also followed by Semsarha and colleagues for the prediction of DNA damage in a variety of studies: from Auger emitter radionuclides ( 123 I and 125 I) [54], from 60 Co gamma rays [55,56] and from ultrasoft X-rays [57].…”
Section: The Cylinder Volumes Approachmentioning
confidence: 99%
“…The authors demonstrated the reasonable agreement on the number of strand breaks per radionuclide decay between Geant4-DNA and theoretical and experimental works from the literature, underlining the applicability of Geant4-DNA for nanodosimetry. They also recommended the usage of accurate geometrical representations of DNA for reliable predictions of indirect effects [54].…”
Section: The Cylinder Volumes Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The βparticle receives a maximum energy of 157 keV and travels around 0.1 mm away [9] from the 14 N nucleus while the physical and chemical effects of the transmuted 14 N have effects on the nanometre scale. While Monte Carlo methods [15][16][17][18] are routinely applied to compute the stochastic effects induced by β-particles in biological systems, the local effects due to transmutation have not been studied using atomistic simulation. Indeed, aside from calculations of beta-decay in solids [19][20][21], and some early work on decay-induced excited states in molecules [22,23], we are unaware of any remotely similar studies.…”
Section: Andmentioning
confidence: 99%